2006
DOI: 10.1145/1124706.1121432
|View full text |Cite
|
Sign up to set email alerts
|

Back to basics in CS1 and CS2

Abstract: This paper describes a significant redesign of the introductory courses at the University of Washington that has led to increased enrollments, increased student satisfaction and an increase in the number of women admitted to the CS major. The new courses are still taught in Java, but they represent a return to the basics that were emphasized in the pre-Java era. The biggest changes have occurred in the CS1 course where we have replaced an "objects early" curriculum with a more traditional procedural approach u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There are surveys on which paradigms are in use: Aleksić and Ivanović [14] note that while most European institutions support object-orientation, most of their introductory courses use the procedural paradigm. There are papers comparing the procedural and object-oriented paradigms [213,544,684], sometimes with the former preceding the latter in a single course [302]. There are papers comparing the functional and object-oriented paradigms [124,246].…”
Section: Figure 12: Number Of Publications Per Year Focusing On Paradigmmentioning
confidence: 99%
“…There are surveys on which paradigms are in use: Aleksić and Ivanović [14] note that while most European institutions support object-orientation, most of their introductory courses use the procedural paradigm. There are papers comparing the procedural and object-oriented paradigms [213,544,684], sometimes with the former preceding the latter in a single course [302]. There are papers comparing the functional and object-oriented paradigms [124,246].…”
Section: Figure 12: Number Of Publications Per Year Focusing On Paradigmmentioning
confidence: 99%
“…Much research has been done to explain the traditional failure and dropout rate of students in these early programming units, often responsible for the dropout of students in undergraduate courses [2,3] and also to improve retention in the major [4,5]. This problem concerns researchers and teachers who try in various ways to combat poor results and contribute to the success of the teaching-learning process, sometimes adapting the design of the units and learning objectives [6][7][8]. The Association for Computing Machinery (ACM) and Institute of Electrical and Electronics Engineers (IEEE) curriculum recommendations are a powerful tool for those who must design courses and more precisely those curricular units.…”
Section: Introductionmentioning
confidence: 99%
“…The first study by Decker (2003) has found no difference in student performance between the two approaches. The second study by Reges (2006) has found significant gains in student satisfaction and enrolment after replacing the object oriented programming first curriculum with a procedural approach. The third study by Vilner (2007) has found no significant gains in student performance between the two approaches.…”
Section: Literature Reviewmentioning
confidence: 99%